2019
DOI: 10.1080/15592294.2019.1695332
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of cytosine-specific 5-hydroxymethylation in normal breast tissue

Abstract: Despite recent evidence that 5-hydroxymethylcytosine (5hmC) possesses roles in gene regulation distinct from 5-methylcytosine (5mC), relatively little is known regarding the functions of 5hmC in mammalian tissues. To address this issue, we utilized an approach combining both paired bisulfite (BS) and oxidative bisulfite (oxBS) DNA treatment, to resolve genome-wide patterns of 5hmC and 5mC in normal breast tissue from disease-free women. Although less abundant than 5mC, 5hmC was differentially distributed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 100 publications
(144 reference statements)
1
11
0
Order By: Relevance
“…Previous reports have showed that the downregulation of TET2 expression and 5hmC levels is an epigenetic hallmark of multiple types of cancers [ 21 , 40 , 41 , 42 ]. Dysregulation of the TET2/5hmC pathway promotes epithelial–mesenchymal transition (EMT), chemotherapy resistance, proliferation, invasion, and metastasis during breast cancer pathogenesis [ 43 , 44 , 45 ]. Based on the afore-mentioned regulatory mechanism, we speculate that TET2 loss may facilitate immune evasion by breast cancer cells through upregulating PD-L1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have showed that the downregulation of TET2 expression and 5hmC levels is an epigenetic hallmark of multiple types of cancers [ 21 , 40 , 41 , 42 ]. Dysregulation of the TET2/5hmC pathway promotes epithelial–mesenchymal transition (EMT), chemotherapy resistance, proliferation, invasion, and metastasis during breast cancer pathogenesis [ 43 , 44 , 45 ]. Based on the afore-mentioned regulatory mechanism, we speculate that TET2 loss may facilitate immune evasion by breast cancer cells through upregulating PD-L1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike methylcytosine, 5hmC concentrates in gene bodies and enhancers and is associated with increased gene expression [ 13 15 ]. 5hmC tends to be depleted in promoter CpG islands and is instead observed in the flanking CpG shores and shelves [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…5mC is oxidized to form hydroxymethylcytosine (5hmC), formylcytosine (5fC) and carboxylcytosine (5caC). 5mC and 5hmC have different functional roles: 5mC is present in heterochromatin and euchromatin and generally represses gene expression 17 whereas 5hmC is mainly present in euchromatin and is associated with the mostly highly transcribed gene bodies and their enhancers 18,19 , as well as with poised enhancers about to transition from inactive to active 20 . 5mC and 5hmC have differential a nity to epigenetic readers; for instance, methyl binding proteins (MBD) preferentially bind 5mC.…”
Section: Introductionmentioning
confidence: 99%